Efektivitas Program Ketahanan Pangan Di Desa Tengin Baru Kecamatan Sepaku Kabupaten Penajam Paser Utara (Studi Kasus Program Pengadaan Bibit Ikan) - Henny Erika Suryaningsih; Budiman, Budiman (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
This research aims to determine and describe the effectiveness of the food security program in Tengin Baru Village, with a special focus on the fish seed provision program in RT.03, RT.06, RT.12, RT.19, and RT.22. This research highlights efforts to strengthen food and nutrition security which includes several main aspects, namely accuracy of program targets, program outreach, program objectives, and program monitoring, through policies from the Ministry of Villages in the form of a food security program. Apart from that, this research also identified factors that hampered Tengin Baru Village's efforts to implement the program. The data collection technique used in this research is purposive sampling, which allows researchers to select samples deliberately according to the research objectives. The research results show that the implementation of the food security program in Tengin Baru Village has been carried out as well as possible in accordance with existing provisions. Various efforts have been made, including through socialization of the program to the community and regular monitoring to ensure the success of the program. However, this research also revealed several inhibiting factors in developing this program. These factors include the lack of education provided to the community regarding the importance of food security, population habits that do not fully support this program, and limited availability of land for fish cultivation. In addition, this research emphasizes the importance of the active role of various parties, including the village government, community and related institutions, in overcoming these obstacles.